Operasi Bukti Pelanggaran (Tilang) dalam Berlalu Lintas terhadap Perilaku Masyarakat - Dwinanda Linchia Levi Heningdyah Nikolas Kusumawardhani (LPPM Universitas 17 Agustus 1945 Semarang, 2023)
Traffic problems are problems faced by developed countries as well as developing countries like Indonesia. However, in Indonesia, the problems that are often encountered nowadays are becoming more severe and bigger than in previous years, including accidents, congestion and air pollution as well as traffic violations. There are at least three factors that influence traffic law enforcement, namely: Judicial Factors, Law Enforcement Factors and Community Legal Culture Factors. In order for the law to have an influence on attitudes or behavior, certain conditions are required, namely: the law must be communicated; position to behave, meaning the things that motivate people to behave in a certain way. Fines alone are not effective in building a culture of safe driving. The government needs to make legal breakthroughs, both in the legal drafting aspect and the system that regulates implementation in the field.